Study regarding the influence of the pandemic on the junior basketball training program - Olanescu, M.; Popa, C. (Science, Movement & Health, 2021)
It is well known that the pandemic has affected all areas of activity, including sport at all levels of training and participation, especially during periods of total disruption of sports activities due to special measures introduced during the lockdown period. Aim. The purpose of this study was to analyze how the training program and participation in competitions of junior basketball players were influenced and affected by the pandemic. Methods. In order to identify the training models used and the differences that existed in terms of the training program during the pandemic between the players who practice performance basketball at junior level in Romania, we conducted an investigation based on the sociological investigation. We used the quantitative research method, namely the technique of administering the questionnaires by sociological survey. Results. The results of the study show that the pandemic severely affected the training period of junior basketball players (73% of the respondents). If before the pandemic, 88.2% of the respondents did training 3-5 times a week, for at least one and a half hours, during the pandemic, for a period of 3-4 months, 31.6% of them did not train at all. Conclusions. For both coaches and players, the pandemic was a challenge to find solutions to continue the training program and to maintain their level of physical and technical training. Most coaches kept in touch with their players, online and face to face, and offered them an individualized physical training program.